Fundamental insights into the threshold characteristics of organic field-effect transistors. (5th January 2015) - Jung, Sungyeop; Kim, Chang-Hyun; Bonnassieux, Yvan; Horowitz, Gilles
Abstract: We physically model the threshold characteristics of organic field-effect transistors (OFETs) using a two-dimensional finite-element method. The transfer characteristics are simulated for staggered OFETs with various electronic structures. A reliable method to extract a structure-unique threshold voltage is presented based on the second-derivative method. By changing the hole injection barrier height in such a manner that the flat-band voltage, defined from the difference of Fermi levels of gate and source electrode, is kept constant, we demonstrate a direct impact of the hole injection barrier height on the threshold voltage. Simulated charge carrier distribution shows the two-dimensional nature of channel creation process and physical insights into the threshold characteristics of OFETs.